Characteristic of Cellulose Isolated From Papyrus Fibers (Borrasus flabelifer L) And Its Citrate Ester - Anna Apriani Maniuk Solo; Masruri MASRURI; Barlah Rumhayati (The Journal of Pure and Applied Chemistry Research, 2018)
The chemical modification using esterification method to modification the papyrus fiber cellulose with citric acid was studied. Parameters investigated included the citrate acid concentration (between 0.3 to 0.6 M), and reaction temperature (from 110 to 140o C). The ester cellulose, which was a new product reaction between citric acid and cellulose, had Substitution Degree (SD) from 0.088 to 1.147 and yield from 73.75% to 97.73%. The esterification product was analyzed with FTIR spectrophotometer and Scanning Electron Microscopy (SEM) to identify the functional groups and the morphology of ester cellulose. Based on this research, modified cellulose have the peak of ester carbonyl functional group (C=O) at 1740.43 cm-1 and O-H alcohol functional group (O-H) at band 3406.82cm-1. Modification with citric acid 0.6 M at 120o C is the best condition to get the high DS value 1.147 in 97.73 yield as a brown powder.